Antioxidant Activity of Aceh Curry Leaves (Murraya Koenigii) Extracted Using Various Solvents - Desy Anggriani; Lisa Azila; Cut Meurah Rosnelly; Hisbullah Hisbullah; Syaubari Syaubari; Teuku Mukhriza (Journal of Applied Technology, 2023)
Free radicals are molecules that are highly reactive and contain unpaired electrons. These molecules are harmful to healthy cells. Antioxidants have the ability to neutralise free radicals by donating one of their electrons to the molecules that make up free radicals. This prevents free radicals from wreaking havoc on healthy cells. Curry leaf, also known as Murraya Koenigii, is a member of the Rutaceae family and is a spice that is commonly used. By gauging the degree to which various solvents and ratios are able to extract antioxidants from curry leaves, the objective of this study is to find the optimal solvent and combination for doing so. A Soxhlet and a solvent mixture consisting of hexane, chloroform, and ethanol in a ratio of 1:10 were used to extract the anti-oxidant components of curry leaves. With a yield percentage of 30.53 percent, the ethanol solvent proved to be the most efficient of the three in terms of extracting antioxidants from the sample. Not only did extracts of curry leaves obtained from the ethanol solvent have the best yield (when compared to extracts derived from other solvents), but they also have the highest levels of inhibition (54.42%) and antioxidant activity (40.667 ppm) when it comes to catching free radicals.